2021
DOI: 10.1111/mec.16010
|View full text |Cite
|
Sign up to set email alerts
|

Lichen fungi do not depend on the alga for ATP production: A comment on Pogoda et al. (2018)

Abstract: Lichen fungi live in a symbiotic association with unicellular phototrophs and most have no known aposymbiotic stage. A recent study in Molecular Ecology postulated that some of them have lost mitochondrial oxidative phosphorylation and rely on their algal partners for ATP. This claim originated from an apparent lack of ATP9, a gene encoding one subunit of ATP synthase, from a few mitochondrial genomes. Here, we show that while these fungi indeed have lost the mitochondrial ATP9, each retain a nuclear copy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In subsequent decades, A. fallacina has continued to be accepted as a distinct species endemic to the Appalachian Mountains (e.g., Dey, 1976, 1978; Lendemer & al., 2017; Tripp & Lendemer, 2019). It has even been used in studies of genomic streamlining in lichen symbioses (Pogoda & al., 2019; Tagirdzhanova & al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In subsequent decades, A. fallacina has continued to be accepted as a distinct species endemic to the Appalachian Mountains (e.g., Dey, 1976, 1978; Lendemer & al., 2017; Tripp & Lendemer, 2019). It has even been used in studies of genomic streamlining in lichen symbioses (Pogoda & al., 2019; Tagirdzhanova & al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Berdan et al (2021) propose a framework for developing a better understanding of different mutation types, their tendency to be costly or beneficial, and their evolutionary consequences.Much of this year's discussions have centered on the analysis and interpretation of metagenomic data. A more complete analysis of lichen metagenomic data fromPogoda et al (2018) confirmed that genes missing from certain lichenized fungal species mitochondrial genomes have been moved to the fungal nuclear genome(Keepers et al, 2021;Tagirdzhanova et al, 2021). Tercel et al (2021) discuss the challenges of diet analysis using DNA metabarcoding in omnivores with diverse and varied diets.…”
mentioning
confidence: 99%